THE INFLUENCE OF THE SHAPE OF THE INGOT AND THE VACUUM ON THE SULPHUR CONTENT IN WHEEL STEEL KP-2 - Shapovalova, O. M.; Deineha, A. V. (Science and Transport Progress, 2009)
From positions of thermodynamics the conditions of formation of sulfides in the steels are described. The regularity of sulfur distribution of in the industrial vacuumized bars from the wheel steel of mark КП-2 is first elucidated. The chemical composition of non-metal inclusions in the wheel steel produced according to different technologies is determined.